Letter to the Reader - Abramowicz, Anete (Revista Eletrônica de Educação, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.14244/198271991194 Letter to the Reader